Protruding urethral polypoid hemangioma - Hysni Jashari; Sadik Llullaku; Božidar Župančić; Baton Kelmendi; Suzana Manxhuka; Nexhmi Hyseni (Elsevier, 2018)
Hemangiomas are the most common tumours of infancy and early childhood. They are not usually present at birth but appear in the neonatal period. Urethral hemangiomas are rare benign vascular tumours varying in size and they present with symptoms like urethral bleeding and/or haematuria. Vascular anomalies are manifested clinically by a large and varying clinical discoloration to large debilitating lesions that can compromise an organ and sometimes result in a life-threatening condition. Treatment of these tumours depends on the size and location. We report a case of a one and a half year old Kosovo Albanian boy presenting with a protruding tumour through external urethra that after pathology was confirmed to be a urethral polypoid hemangioma. This case, to our knowledge, is a rare case of protruding polypoid hemangioma of the external urethra reported in the literature. The lesion presented as a reddish-pink formation protruding through external urethra on physical examination. Doppler ultrasound described a high vessel density hemangioma.Physical examination is usually sufficient for diagnosis. Biopsy should be performed in any vascular lesion in which malignancy is suspected. Although approximately 20% of hemangiomas cause destructive, obstructive or endangering complications, less than 1% are truly life-threatening.